Learning to produce and transcribe cardinal vowels: speech and language therapy students' perception of task difficulty. - Whitworth, Nicole (Clinical Linguistics & Phonetics, 2025)
Learning vowel transcription skills is crucial to function as a Speech and Language Therapist (SLT). However, vowel transcription is commonly regarded as particularly difficult and therefore often avoided. Despite the importance of accurate transcriptions, little is known about all the factors that influence the process of learning vowel transcription, which usually includes the learning of the Cardinal Vowel (CV) system. There are only a few studies that investigate how CVs are learnt and what factors lead to successful learning. The current study reports students' perceived difficulty of producing and transcribing CVs as a first step to identify how perceived difficulty affects phonetic learning. Perceived difficulty ratings for the production and transcription of 12 CVs collected from 155 students studying towards a qualification as an SLT were analysed. The results show that the classificatory features correlate with the perceived task difficulty of production and transcription. Implications for teaching are outlined.